RESEARCH OF THE MOTIVATIONAL ORIENTATION OF CADETS TO MILITARY PROFESSIONAL ACTIVITIES - Pavelko, Iryna; Belovodov, Ihor (Honor and Law, 2022)
The article considers theoretical and empirical aspects of motivation of military and professional activity. It is proved that the professional motivation of future servicemen is a system of incentive mechanisms aimed at mastering the military profession and self-realization in it. The main motivational aspects of choosing a military specialty and social characteristics of respondents are studied. The study of motivation for military service was conducted in the framework of research work «Improvement of the regulatory framework for physical training of servicemen of the Armed Forces of Ukraine and physical education of pre-conscription youth to ensure physical readiness for service» (reg. № 0119U001816). To solve the tasks of the study, 195 cadets of the Military Academy were surveyed and tested using the scale «military and professional orientation» of MPQ «Adaptability-200» and Questionnaire on the study of motivation for military service, which contains 2 blocks: the first block concerns the motivation to choose a military profession , the second block contains questions about social characteristics: the social background of parents, perceptions of military service, as well as the reasons that influenced the professional choice. The study of the motivational sphere of cadets revealed that the dominant motives of service in the Armed Forces of Ukraine are: patriotic motive and love for the Motherland – 122 respondents (88,20 %); in the second place is the motive of the prestige of the military profession – 74 people (37,94 %); in the third place – the motive of receiving social guarantees, benefits and stable financial situation – 70 people (35,89 %). A study of the motivational sphere of cadets by faculties shows that the leading motive for studying at a military university, namely the Military Academy (Odesa) is a patriotic motive, in particular: 79,16 % of cadets of the Airborne Assault Forces faculty; 69,38 % of cadets of the faculty of specialists of the military reconnaissance and special forces; 55,26 % at the faculty of Missile and artillery armament specialists; 48,33 % of respondents of the faculty of Logistics specialists.